The Teachers’ perception of Continuous Professional Development “CPD” effectiveness in Higher Education in Kurdistan: CPD - Mahdi Azeez Qader (IJER (Indonesian Journal of Educational Research), 2019)
Abstract This research project is a case study conducted to investigate "Teachers’ perceptions of CPD effectiveness in Higher Education in Kurdistan". This will show the impact of CPD at the institutional and individual level, as well as to highlight the current CPD policies at the selected organization. The participants of this study were 120 teachers. The research took a quantitative approach and data were collected using close-ended questionnaires. For data analysis the Statistical Package for the Social Sciences (SPSS) was used. The findings indicate that CPD has a crucial role in the delivery of teaching. However, practitioners note that the sector dynamic is not organized. In other words, findings revealed a mismatch between individual needs and CPD policy, for instance, lack of ICT. In addition, it might be that policy makers are not addressing issues that have the potential to impact upon the higher education sector.